1998
DOI: 10.1007/s004380050665
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a chromosomally integrated, single-copy GFP gene in Candida albicans, and its use as a reporter of gene regulation

Abstract: Genetically engineered versions of the GFP gene, which encodes the green fluorescent protein of Aequorea victoria, were placed under the control of the constitutively active Candida albicans ACT1 promoter and integrated in single copy into the genome of this pathogenic yeast. Integrative transformants in which one of the two ACT1 alleles had been replaced by a GFP gene exhibited a homogeneous, constitutive fluorescent phenotype. Cells expressing GFP with the wild-type chromophore exhibited very weak fluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
65
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 34 publications
2
65
0
Order By: Relevance
“…Study approval was provided by the local ethics committee (Umbria Regional Hospital Ethics Committee, CEAS Umbria), and informed written consent was obtained from all participants in accordance with the Declaration of Helsinki. The CAG31A C. albicans mutant strain expressing the GFP gene was obtained as described 42 . When observed by fluorescence microscopy, both yeasts and hyphae of the CAG31A strain were intensively fluorescent 43 .…”
Section: Methodsmentioning
confidence: 99%
“…Study approval was provided by the local ethics committee (Umbria Regional Hospital Ethics Committee, CEAS Umbria), and informed written consent was obtained from all participants in accordance with the Declaration of Helsinki. The CAG31A C. albicans mutant strain expressing the GFP gene was obtained as described 42 . When observed by fluorescence microscopy, both yeasts and hyphae of the CAG31A strain were intensively fluorescent 43 .…”
Section: Methodsmentioning
confidence: 99%
“…Plasmid pGFP41 has been described previously (18). It contains a GFP gene, genetically modified for expression in C. albicans under control of the SAP2 promoter, and the URA3 selection marker in the vector pBluescript.…”
Section: Methodsmentioning
confidence: 99%
“…To avoid recombination between the MDR1 promoter from strain CAI4 and MDR1 upstream sequences in the host strains, integration was targeted to an ectopic site in the genome. The CDR4 locus was chosen for integration, as this region had been characterized previously by our group and it had been shown that inactivation of one of the CDR4 alleles did not result in a detectable phenotype (18). In addition, CDR4 expression levels did not differ between the fluconazolesusceptible and resistant isolates (9).…”
mentioning
confidence: 99%
“…Primers CB51F and CB51R were designed to bind immediately up and downstream of the STOP codon, respectively, and to reverse-amplify the plasmid sequence, into which a XhoI/SpeI PCR fragment (produced with primers CB44F and CB44R) of GFP (Morschhauser et al, 1998) was cloned, creating plasmid pCB105. pCB105 was digested with BstEII for directed integration at the endogenous TUB1 locus, creating full-length 3Ј-tagged TUB1-GFP, under control of its own promotor, and a 5Ј-truncated copy.…”
Section: Cloning and Plasmid And Strain Productionmentioning
confidence: 99%